Elucidating the interplay between metabolites and microorganisms in the spermosphere of common bean (Phaseolus vulgaris L.) seeds - Chandrodhay Saccaram; Marie Simonin; Stéphanie Boutet; Céline Brosse; Shuang Peng; Tracy François; Boris Collet; François Perreau; Delphine Sourdeval; Coralie Marais; Matthieu Barret; Loïc Rajjou; et al. (mSystems)
ABSTRACT The spermosphere, the dynamic interface surrounding germinating seeds, is shaped by the intricate interplay between seed-exuded natural compounds and seed-associated microbial communities. In this work, we provide the first comprehensive metabolomic and microbiome characterization of common bean (Phaseolus vulgaris) spermosphere of eight genotypes produced in two contrasted production regions. Through an integrated approach, we explored the metabolomic and microbiota composition in the spermosphere of germinating common bean seeds and elucidated their environmental and genotype regulation. We detected and analyzed 2,467 metabolite features (Mf) through untargeted metabolomics categorized into fourteen metabolic categories, highlighting the prevalence of amino acids, flavonoids, and terpenoids. Genotype was the key factor influencing the chemical composition of the spermosphere. Furthermore, we identified 19 bacterial families and 23 fungal families inhabiting the spermosphere, with both genotype and seed production location exerting varying degrees of influence on microbial community composition. Through a multiscale integrated approach, we revealed specific associations between metabolites and microorganisms, such as negative correlation between flavonoids and Bacillus spp., emphasizing the genotype-dependent nature of these interactions. This comprehensive investigation sheds light on the mechanisms underlying seed germination and the complex interactions between plant genotypes, seed exudates, environmental conditions, and microbial communities in the spermosphere. These findings provide a framework for developing innovative strategies to promote seed health and sustainable crop production.IMPORTANCEThe spermosphere, the dynamic interface around germinating seeds, is shaped by the intricate interplay between seed-exuded compounds and microbial communities. Despite the importance of these interactions for eventual seedling emergence and health, little knowledge is available on the subject. We are the first to comprehensively analyze the chemical and microbial diversity of the spermosphere of Phaseolus vulgaris (common bean). We identified thousands of primary and specialized metabolites, highlighting their diversity but largely unknown roles in germinating seed-environment interactions. We revealed significant genotype-driven differences in the chemical composition as well as the influence of both genotype and seed production location on microbial community structure in the spermosphere. Our metabolome-microbiome integrative analysis suggests that common bean shapes the spermosphere microbiome through specific seed exudates. This research advances our understanding of the metabolic capabilities and ecological roles of seed microbiota within the spermosphere, contributing to our understanding of seed health and vigor.